2021
DOI: 10.3390/ijerph18126468
|View full text |Cite
|
Sign up to set email alerts
|

Infection Prevention Performance among In-Flight Cabin Crew in South Korea

Abstract: COVID-19 was declared a worldwide pandemic in 2020; thus, preventing in-flight infection transmission is important for stopping global spread via air travel. Infection prevention (IP) performance among aircraft cabin crew is crucial for preventing in-flight transmission. We aimed to identify the level of IP performance and factors affecting IP performance among aircraft cabin crew during the COVID-19 pandemic in South Korea. An online survey was conducted with 177 cabin crew members between August and Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Finally, this may be due to the in-flight working process. When patients have a suspected infectious disease, the team leader handles them directly or instructs other cabin crew members according to the airline policy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, this may be due to the in-flight working process. When patients have a suspected infectious disease, the team leader handles them directly or instructs other cabin crew members according to the airline policy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flight-duty schedule was decided on a monthly basis owing to the closure of the airline, but approximately 50% of flight duties were carried out during a quarantine period, which may have caused anger and anxiety. A previous study reported that approximately 11% of Korean cabin crews experienced quarantine because of contact with suspected and confirmed cases of COVID-19 [ 8 ]. In addition, when a cabin crew stays abroad for flight duty, many countries and airlines require them to not leave the hotel and eat alone in their hotel rooms [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper health education should be given to these contacts regarding the patient to minimize panic and fear of infection control procedures. Furthermore, to reduce the transmission of diseases, health education for cabin crew members is essential (Ryu et al, 2021). The KAIA Preventive Medical Center asks for contacts to be isolated or quarantined during the incubation period and samples are taken from them to exclude infection and provide the necessary medical services to those in need.…”
Section: Contact Tracingmentioning
confidence: 99%
“…They have the most contact with passengers of any airline employee and are responsible for the safety of all passengers onboard the aircraft, both sick and healthy. During the COVID-19 pandemic and post-pandemic period, cabin crew were responsible for preventing inflight transmission of the disease by implementing appropriate infection control measures required by airline companies [4,5]. However, cabin crew are not professionals in the infection prevention (IP) field, because they are not medical personnel.…”
Section: Introductionmentioning
confidence: 99%